2020
DOI: 10.1016/j.bja.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in rhythmic and arrhythmic neural signatures in the subthalamic nucleus induced by anaesthesia and tracheal intubation

Abstract: Background: Subcortical structures, including the basal ganglia, have been proposed to be crucial for arousal, consciousness, and behavioural responsiveness. How the basal ganglia contribute to the loss and recovery of consciousness during anaesthesia has, however, not yet been well characterised. Methods: Twelve patients with advanced Parkinson's disease, who were undergoing deep brain stimulation (DBS) electrode implantation in the subthalamic nucleus (STN), were included in this study. Local field potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…Several and relevant points related to 1/f should be discussed and properly considered when interpreting any pathological changes. In particular, we would like to emphasize that 1/f may flatten as an effect of aging (Dave et al, 2018; or may steepen in pharmacological induced unconsciousness (Colombo et al, 2019;Gao et al, 2017;Huang et al, 2020) or may discriminate between different states of consciousness (present/reduced or abolished) (Colombo et al, 2019). Moreover, 1/f slope has been shown to be a marker of states of reduced arousal, including sleep stages as well as anesthesia (Lendner et al, 2020;Miskovic et al, 2019;Muthukumaraswamy and Liley, 2018;Pereda et al, 1998;Shen et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Several and relevant points related to 1/f should be discussed and properly considered when interpreting any pathological changes. In particular, we would like to emphasize that 1/f may flatten as an effect of aging (Dave et al, 2018; or may steepen in pharmacological induced unconsciousness (Colombo et al, 2019;Gao et al, 2017;Huang et al, 2020) or may discriminate between different states of consciousness (present/reduced or abolished) (Colombo et al, 2019). Moreover, 1/f slope has been shown to be a marker of states of reduced arousal, including sleep stages as well as anesthesia (Lendner et al, 2020;Miskovic et al, 2019;Muthukumaraswamy and Liley, 2018;Pereda et al, 1998;Shen et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…The latter is supported by multiple studies showing that aperiodic exponents in non-invasive EEG and invasive LFP measurements were modulated by sleep and anaesthesia, with lower exponents, corresponding to slower decay of power with increasing frequencies, during the conscious state, which is linked with increased excitation. Inversely, higher aperiodic exponents, corresponding to faster decay of power with increasing frequencies, were observed during the unconscious state (NREM sleep, anaesthesia), which is linked with more inhibition (Colombo et al, 2019; Huang et al, 2020; Lendner et al, 2020; Miskovic et al, 2019; Niethard et al, 2016; Waschke et al, 2021). In addition, Gao and colleagues found that theta cycle-modulated E/I changes in the rat hippocampus are reflected in the per-cycle PSD exponent of hippocampal LFPs calculated at different theta phases (peaks or troughs) confirming the E/I hypothesis for LFPs (Gao et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12][13] However, whether the NAc participates in regulating states of consciousness in GA remains largely unknown. Notably, a few recent laboratory and clinical studies have begun to highlight the importance of the basal ganglia and limbic system in the mechanisms of action of GA; 3,14,15 interestingly, the NAc acts as an important interface between these two systems. 16,17 Recent neuroimaging evidence has also suggested that the NAc may be essential for modulating anesthetic-induced unconsciousness.…”
Section: Introductionmentioning
confidence: 99%